2019
DOI: 10.1039/c8pp00534f
|View full text |Cite
|
Sign up to set email alerts
|

A combination of photodynamic therapy and antimicrobial compounds to treat skin and mucosal infections: a systematic review

Abstract: aPDT combined with antimicrobials could be promising to manage skin and mucosal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 36 publications
0
59
0
Order By: Relevance
“…An experimental study with 21 PLWHA showed that fluconazole did not prevent recurrence of oral candidiasis when they were reevaluated within 30 days, whereas in patients receiving PDT, there was no recurrence of the lesion during the same reevaluation period 14 . The combination of PDT and fluconazole was effective in reducing C. albicans colonies in in vitro 10,11 and in vivo 12,13 studies. In this study, participants 015 and 018, respectively, received PDT/nystatin and PDT/ fluconazole exhibited a reduction in oral candidiasis severity ratings when reassessed after 14 days.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…An experimental study with 21 PLWHA showed that fluconazole did not prevent recurrence of oral candidiasis when they were reevaluated within 30 days, whereas in patients receiving PDT, there was no recurrence of the lesion during the same reevaluation period 14 . The combination of PDT and fluconazole was effective in reducing C. albicans colonies in in vitro 10,11 and in vivo 12,13 studies. In this study, participants 015 and 018, respectively, received PDT/nystatin and PDT/ fluconazole exhibited a reduction in oral candidiasis severity ratings when reassessed after 14 days.…”
Section: Discussionmentioning
confidence: 95%
“…This technique has shown to be promising in reducing C. albicans colonies in in vitro [9][10][11] and in vivo 12,13 assays. PDT was also effective in the treatment of oral candidiasis in PLWHA, without causing side effects, both isolated 14 and when associated with topical antifungals 15 .…”
Section: Introductionmentioning
confidence: 99%
“…In the management of cancer, PDT has been used to deliver localized bursts of cytotoxic O 2 to tissues marked for destruction [91]. It has also been studied for antimicrobial use in skin and mucosal infections with success [92,93]. Fan et al described its use to deliver 5-aminolevulinic acid for the treatment of rosacea, a chronic skin condition with unknown pathogenesis [94].…”
Section: Phototherapeuticsmentioning
confidence: 99%
“…An emerging strategy to fight hospital-acquired infections is the so-called antimicrobial photodynamic inactivation (aPDI) (14)(15)(16)(17). This approach has been developed in parallel with the photodynamic therapy (PDT) of cancer (18,19), although in recent times it has attracted a renewed interest (14,15,(20)(21)(22)(23)(24)(25)(26). It is based on the killing of microorganisms by reactive oxygen species (ROS), for instance singlet oxygen and radicals, which in turn are generated due to the absorption of light by a photosensitizer in the presence of oxygen.…”
Section: Introductionmentioning
confidence: 99%